Revealing The Theme of Regret Through Symbolism and Narrative Structure: A New Critical Study of Matt Haig’s The Midnight Library - Rozadi, Farhan; Rizano, Gindho (Program Studi Sastra Inggris, 2025)
This study analyzes Matt Haig’s The Midnight Library (2020) using a New Criticism approach to reveal how regret is transformed into acceptance through symbolism and narrative structure. A qualitative method with close reading was employed, focusing on the novel’s formal elements and supported by relevant secondary sources. The findings show that recurring symbols such as the library, green books, chess, and whales together with the cyclical narrative structure, create organic unity that reflects Nora Seed’s struggle with regret and her eventual self-acceptance. The study concludes that the novel demonstrates how formal elements interact to affirm the theme of embracing self-worth through the reconciliation of regret.